Loose tooth - Schaefer, Lola M.; Wickstrom, Sylvie (New York : HarperCollins Publishers, 2004)
A young child experiences a loose tooth for the first time and eagerly waits for it to come out.
Keywords: Teeth -- Juvenile fiction